2023
DOI: 10.3390/ani13081285
|View full text |Cite
|
Sign up to set email alerts
|

Natal Origin and Spatiotemporal Distribution of Leatherback Turtle (Dermochelys coriacea) Strandings at a Foraging Hotspot in Temperate Waters of the Southwest Atlantic Ocean

Abstract: Leatherback turtles migrate long distances between nesting beaches and distant foraging areas worldwide. This study analyzes the genetic diversity, life history stage, spatiotemporal distribution, and associated threats of a foraging aggregation in the Southwest Atlantic Ocean. A total of 242 leatherbacks stranded or bycaught by artisanal fisheries were recorded from 1997 to 2021 in Uruguay, with sizes ranging from 110.0 to 170.0 cm carapace lengths, indicating that the aggregation is composed of large juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Once dead, small juvenile green turtles might be more vulnerable to scavenging and might therefore undergo a more rapid decomposition process than large loggerhead and leatherback turtles, thus reducing the chance of carcasses washing ashore. Indeed, the few green turtles observed in this study were severely decomposed in contrast to those found in Uruguay and southern Brazil, where living or freshly dead juvenile green turtles represent more than 50% of the strandings (Monteiro et al, 2016;Vélez-Rubio et al, 2013). Other possible explanations could be differences in turtle abundances (i.e., green turtles might be less abundant in the study area than the rest of the species) or a spatial segregation between green, loggerhead and leatherback turtles (although studies on the broad habitat use of these species suggest the opposite; López-Mendilaharsu et al, 2009;, 2016.…”
Section: Interpretation Of Sea Turtle Stranding Patterns and Driversmentioning
confidence: 52%
See 3 more Smart Citations
“…Once dead, small juvenile green turtles might be more vulnerable to scavenging and might therefore undergo a more rapid decomposition process than large loggerhead and leatherback turtles, thus reducing the chance of carcasses washing ashore. Indeed, the few green turtles observed in this study were severely decomposed in contrast to those found in Uruguay and southern Brazil, where living or freshly dead juvenile green turtles represent more than 50% of the strandings (Monteiro et al, 2016;Vélez-Rubio et al, 2013). Other possible explanations could be differences in turtle abundances (i.e., green turtles might be less abundant in the study area than the rest of the species) or a spatial segregation between green, loggerhead and leatherback turtles (although studies on the broad habitat use of these species suggest the opposite; López-Mendilaharsu et al, 2009;, 2016.…”
Section: Interpretation Of Sea Turtle Stranding Patterns and Driversmentioning
confidence: 52%
“…), thus plastic ingestion does not seem to be a plausible cause of mortality, neither directly (i.e., obstructions) nor indirectly (i.e., debilitation). On the other hand, there was no evidence of collision with vessels as observed in Uruguay (Vélez‐Rubio et al, 2023).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations